Targeted Chemotherapy: Targeted Chemotherapy of Glioblastoma Spheroids with an Iontronic Pump (Adv. Mater. Technol. 5/2021). Issue 5 (5th May 2021) - Waldherr, Linda; Seitanidou, Maria; Jakešová, Marie; Handl, Verena; Honeder, Sophie; Nowakowska, Marta; Tomin, Tamara; Karami Rad, Meysam; Schmidt, Tony; Distl, Joachim; Birner‐Gruenberger, Ruth; von Campe, Gord; et al.
Abstract : In article number 2001302, Silke Patz, Daniel T. Simon, Rainer Schindl, and co‐workers engineer an electronically‐driven ion pump for the targeted delivery of the charged chemotherapeutic gemcitabine to brain cancer cells. By delivering drug ions over a cation exchange membrane at currents in the nanoampere range, brain cancer cell death and microtumor disintegration is triggered. This local gemcitabine treatment offers a therapeutical window, in contrast to standard treatment.